Structure of a KirBac potassium channel with an open bundle crossing indicates a mechanism of channel gating. - Bavro, V; De Zorzi, R; Schmidt, MR; Muniz, JR; Zubcevic, L; Sansom, M; Vénien-Bryan, C; Tucker, S (2012)
KirBac channels are prokaryotic homologs of mammalian inwardly rectifying (Kir) potassium channels, and recent crystal structures of both Kir and KirBac channels have provided major insight into their unique structural architecture. However, all of the available structures are closed at the helix bundle crossing, and therefore the structural mechanisms that control opening of their primary activation gate remain unknown. In this study, we engineered the inner pore-lining helix (TM2) of KirBac3.1 to trap the bundle crossing in an apparently open conformation and determined the crystal structure of this mutant channel to 3.05 Å resolution. Contrary to previous speculation, this new structure suggests a mechanistic model in which rotational 'twist' of the cytoplasmic domain is coupled to opening of the bundle-crossing gate through a network of inter- and intrasubunit interactions that involve the TM2 C-linker, slide helix, G-loop and the CD loop.